Deliberative Dialogues Between Policy Makers and Researchers in Canada and Australia. (June 2017) - Boydell, Katherine M.; Dew, Angela; Hodgins, Michael; Bundy, Anita; Gallego, Gisselle; Iljadica, Alexandra; Lincoln, Michelle; Pignatiello, Antonio; Teshima, John; Willis, David
Knowledge translation (KT) and implementation science are growing fields in Canada, Australia, and worldwide. Many audiences are targeted as KT knowledge users—policy makers represent one key knowledge user in the health care field. The need for policy makers to understand research and for researchers to understand policy processes is commonly recognized. There is also increasing interest in health policy that focuses on KT as a framework for understanding the use of evidence and, in particular, describing the influence of research on policy along with concepts of coproduction and user involvement. With relationship building central to successful evidence-informed policy, this article explores deliberative dialogue as a potential approach to enhancing KT. It describes two examples of researcher efforts to cultivate relationships and contacts with policy and decision makers via such dialogues and illustrates the inherent opportunities and challenges of doing so.